Comparing Mental Health of School-Age Children with and without Epilepsy - Sayad Noveyri, Marzieh jahani; Oshvandi, Khodayar; Vatandost, Salam (Iranian Journal of Child Neurology, 2019)
Dear Editor-in-Chief The article entitled “Comparing Mental Health of School-Age Children with and without Epilepsy” published in summer 2016 (1) was very interesting and focused on a valuable subject, which indicates the researchers’ scrutiny. We would, therefore, like to express our gratitude to the authors for selecting this subject and to the Iranian Journal of Child Neurology as well